Influence of length, diameter and position of the implant in its fracture incidence: A Systematic Review - Marcelo Coelho Goiato; Agda Marobo Andreotti; Daniela Micheline dos Santos; Adhara Smith Nobrega; Fernanda Pereira de Caxias; Lisiane Cristina Bannwart (Tabriz University of Medical Sciences, 2019)
Background. Implant fractures can cause difficult problems for patients and dentists. This systematic review aimed to determine the influence of some implant parameters on the occurrence of their fracture and to determine the incidence of fractures reported in recent years. Methods. A search was conducted in Pubmed database, from which 12 studies published in the last 12 years were selected. Results. This review reported a 2% incidence of implant fracture. Most implants had been in function between 3 and 4 years until fracture. The studies did not provide necessary information to establish a relationship between the different parameters of implants and the incidence of fractures. Conclusion. Thus, the indication of type, diameter and length of an implant and the bone quality in the region receiving it should be studied and accurately examined for each individual case in order to avoid future failures.